Analisis risiko Rantai Pasok Crude Palm Oil Menggunakan Metode House of Risk (Studi Kasus di PTPN IV Regional II Pagar Merbau) - Prayoga, Rangga Adi; Roessali, Wiludjeng; Nurfadillah, Suryani (Universitas Galuh, 2025)
This study aimed to analyze the level of risk, risk events and risk agents, and risk mitigation strategies for the CPO supply chain at PTPN IV Regional II Pagar Merbau, Pagar Merbau District, Deli Serdang Regency, North Sumatra Province. This research was conducted from September 23 to October 18, 2024, at the Pagar Merbau Palm Oil Mill KSO PTPN IV Regional II Pagar Merbau II Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra Province. The research method used in this study was a case study with quantitative descriptive analysis. The coefficient of variation (CV) method was used to measure the level of production risk. The SCOR method was used to describe the basic supply chain process of CPO products. The HOR phase 1 method was used to identify and assess risk events and risk agents. The HOR phase 2 method was used for risk evaluation and for analyzing mitigation strategies for CPO supply chain risk agents that had been prioritized. The results showed that the level of risk, based on the coefficient of variation for production quantity, was classified as very high at 28.67%. The results of risk identification revealed 17 risk events, 16 risk agents, and 7 priority risk agents with the highest ARP values that needed to be handled improper production target planning (A1), lack of accuracy in human resources (A2), uncertainty in the yield of FFB in the core plantation (A3), non-routine maintenance and untimely overhaul implementation (A10), damaged core roads in the plantation that disrupted FFB delivery (A4), excessive use of shells as fuel (A11), and leakage of stewing equipment due to worn liners (A8). The results identified 8 mitigation strategies to reduce 7 priority risk agents was reviewing the production target plan (PA1), improving roads to facilitate FFB delivery (PA5), enhancing the supervision system and job training for human resources (PA2), conducting regular maintenance audits (PA4), increasing FFB purchases from third parties (PA3), performing routine inspections and minor repairs to maintain machine conditions (PA6), backing up spare parts (PA7), and periodically replacing stew liners (PA2).